ANALYSIS OF THE EFFECT OF SOCIAL MEDIA MARKETING AND BRAND IMAGE ON CONSUMER PURCHASING DECISIONS AT KOPI KENANGAN IN PADANG CITY - Wulanda, Fanny; Salsabila, Nadia Ananda; Nolasary, Mega Putri (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The purpose of this study is to determine the effect of social media marketing and brand image on consumer purchasing decisions at Kopi Kenangan in Padang City. This research uses quantitative research methods with descriptive quantitative research types. Sampling was carried out by non-probability sampling techniques, the technique used was purposive sampling techniques, the number of respondents was obtained by 100 respondents. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. Based on the results of multiple linear regression processed using SPSS version 25.0. The results of the study with a significant level of 5% found that: (1) Social Media Marketing does not have a significant effect on purchasing decisions, (2) Brand image has a positive and significant effect on purchasing decisions, (3) Social Media Marketing and Brand Image simultaneously affect purchase decisions. The result of the coefficient of determination was 55.6% while the remaining 44.4% was effectd by other variables that were not studied in this study